Expanding the search for germline pathogenic variants for breast cancer. How far should we go and how high should we jump? The missed opportunity! - Hikmat Abdel-Razeq (Frontiers Media S.A., 2021)
Since the identification of BRCA1 and BRCA2 genes 3 decades ago, genetic testing and genetic counseling have become an integral part of routine clinical practice. The risk of breast cancer among carriers of germline pathogenic variants, like BRCA1 and BRCA2, is well established. Risk-reducing interventions, including bilateral mastectomies and salpingo-oophorectomies are both effective and have become more acceptable. Many researchers and professional societies view current guidelines as restrictive and may miss many at-risk women, and are calling to expand testing to include all patients with breast cancer, regardless of their personal or family history of cancer, while others are calling for wider adoption to even include all healthy women at age 30 or older. This review will address expanding testing in two directions; horizontally to include more patients, and even healthy women, and vertically to include more genes using next-generation sequencing-based multi-gene panel testing.